The measurement of job satisfaction: An empirical study of frontline employees in the northern cyprus hotel industry - Karatepe, Osman M.; Avcí, Turgay; Karatepe, Tuna; Canozer, Sezen (My University, 2003)
This study investigates the effects of various dimensions on job satisfaction, using a sample of Turkish frontline employees in Northern Cyprus hotels as its setting. Results suggest that pay and supervision have significant positive effects on the job satisfaction of frontline employees, whereas the work itself and physical evidence do not have any significant relationship with job satisfaction. The implications of the results for hotel managers and public policy makers are discussed. © 2003, Taylor & Francis Group, LLC. All rights reserved.
Keywords: Frontline employees; Hotel industry; Job satisfaction; Northern Cyprus